Effect of Dietary Seaweed (Gracilaria pulvinata and Sargassum ilicifolium) on Serum and Mucosal Immunity, Some Growth and Immune-Related Genes Expression, Antioxidant Status, and Fatty Acid Profile in Asian Seabass (Lates calcarifer) - Seyed Hadi Seyedalhosseini; Amir Parviz Salati; Mansour Torfi Mozanzadeh; Christopher C. Parrish; Ali Shahriari; Mina Ahangarzadeh (Aquaculture Nutrition, 2024)
This study was done to appraise the effects of the combination of dietary Gracilaria pulvinata and Sargassum ilicifolium on growth, immunity, and fatty acid profile in Asian seabass (Lates calcarifer). A total of 540 juveniles (36.06 ± 0.05 g) were stocked into eighteen 200 L tanks and divided into six experimental treatments, each in triplicate. Fish were fed diets containing 0 (control), 3% (SW3), 6% (SW6), 9% (SW9), 12% (SW12), and 15% (SW15) mixtures of both seaweeds powder in equal proportions (1 : 1) for 56 days. There was no improvement in weight gain parameters. Serum lysozyme and peroxidase activities in SW9 and SW12 treatments were significantly higher in compare to other treatments. The highest activities of skin mucus lysozyme, alkaline phosphatase, and total protease were observed in the SW12. Liver igf-1, il-1β, il-8, and lysozyme expression showed a rising trend up to SW9 and then decreased. Liver antioxidant enzymes activity and glutathione content showed a similar pattern of changes. Liver total antioxidant capacity was highest in the SW9 treatment, while the lowest value of liver malondialdehyde was observed in the 12% seaweed treatment. The amount of total n-3 polyunsaturated fatty acids, especially docosahexaenoic acid, was higher in the SW12 and SW15 treatments in compare to others. Our findings suggest that adding 9%–12% of Gracilaria and Sargassum seaweed powder to the diet improves serum and mucosal immunity, antioxidant status, and fatty acid profile in L. calcarifer juveniles.